Adjunctive techniques for renal cell carcinoma ablation: an update - Torres, Tiago Paulino; Liakopoulos, Ioanis; Balomenos, Vasilios; Grigoriadis, Stavros; Papakonstantinou, Olympia; Kelekis, Nikolaos; Filippiadis, Dimitrios (Frontiers in Radiology, 2025)
Percutaneous ablation therapies currently play a major role in the management of T1a and T1b renal cell carcinoma (RCC). These therapies include thermal ablative technologies like radiofrequency (RFA), microwave (MWA) and cryoablation, as well as emerging techniques like irreversible electroporation (IRE) and high-intensity focused ultrasound (HIFU). These therapies are safe and effective, with their low complication rate being mostly related to the minimal invasive character. To increase the outcomes and safety of ablation, particularly in the setting of larger tumors, adjunctive techniques may be useful. These include pre-ablation trans-arterial embolization (TAE) and thermal protective measures. TAE is an endovascular procedure consisting of vascular access, catheterization and embolization of renal vessels supplying target tumor, with different embolic materials available. The purpose of combining TAE and ablation is manifold: to reduce vascularization and improve local tumor control, to reduce complications (including the risk of bleeding), to enhance tumor visibility and localization, as well as to improve cost-efficiency of the procedure. Thermal protective strategies are important to minimize damage to adjacent structures, requiring accurate knowledge of anatomy and proper patient positioning. In RCC ablation, strategies are needed to protect the adjacent nerves, as well as the visceral and muscular organs. These include placement of thermocouples, hydro- or gas-dissection, balloon interposition, pyeloperfusion and skin protection maneuvers. The purpose of this review article is to discuss the updated role of ablation in RCC management, to describe the status of adjunctive techniques for RCC ablation; in addition it will offer a review of the literature on adjunctive techniques for RCC ablation. and report upon future directions.